Analysis of the Management Information System of MBKM at Prima Indonesia University Using the Waterfall Method - Kaban, Sari Mutiara; Pincawan, Irma Kristina Br; Pangestu, Fadhil; Silitonga, Theofilus Kristian; K.Nababan, Marlince Novita (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2024)
Implementing MBKM activities in the field has challenges for students and the unavailability of MBKM information within the campus environment is an obstacle to participating in MBKM. This research is to analyze and build a web-based MBKM information system using the Laravel framework and an effective System Development Life Cycle (SDLC) model to support the implementation and monitoring of MBKM activities on campus. Researchers provide solutions to the obstacles faced by students in participating in MBKM activities, so that this program can run more smoothly and achieve the researchers' goals. The SDLC model is a model for developing website-based information systems. SDLC provides a systematic and structured approach to ensure that the software being developed meets requirements. The research results show that the SLDC model produces business processes that need to be developed, namely adding access rights for stakeholders to make it easier to assess study programs, and the need for involvement of system programs (Prodi) for assessing MBKM student activities. Researcher's suggestions for the security of using user accounts and access rights for Human Resources with experience in MBKM activities.